Pengaruh Struktur Kepemilikan dan Ukuran Perusahaan Pada Praktik Perataan Laba - Nur Andiani, A.A. Sagung; Astika, Ida Bagus Putra (E-Jurnal Akuntansi, 2019)
The capital market is growing from time to time. The company issues shares to obtain capital from investors. Profit is one of the main indicators for measuring performance and management accountability. Attention Investors tend to only focus on profit, management realizes that earnings information is the most important thing for a company, so managers are encouraged to practice income smoothing. This study aims to obtain empirical evidence of the influence of ownership structure and firm size on income smoothing practices in manufacturing companies listed on the Indonesia Stock Exchange. The number of samples selected in manufacturing companies is as many as 25 companies, using the purposive sampling method. This research was tested by Logistic Test and the results showed that the structure of managerial ownership and firm size did not affect the income smoothing practice while the institutional ownership structure had a positive effect on income smoothing practices. Keyword s: Income smoothing practices, managerial ownership, firm size